Mechanisms for ensuring the competitiveness of commercial banks in the financial market based on digital financial services - Abdurakhmanova , Matluba (Innovation Science and Technology, 2025)
This article examines the role of digital financial services and their implementation mechanisms in enhancing the competitiveness of commercial banks in the financial market environment. The study analyzes the impact of digitalization of banking services, the development of fintech technologies, and the introduction of digital banking services on the efficiency of banking activities. In the course of the research, methods such as comparative analysis, statistical analysis, a systematic approach, and expert evaluation were applied. The results of the study demonstrate that expanding digital banking services, effectively utilizing fintech technologies, and developing digital customer service infrastructure are among the key factors for increasing the competitiveness of commercial banks in the financial market. In addition, scientifically grounded recommendations were developed to improve the development of digital financial services in the banking system.